Synergism interaction between genetic polymorphisms in drug metabolizing enzymes and NSAIDs on upper gastrointestinal haemorrhage: a multicenter case-control study. (31st December 2022) - Mallah, Narmeen; Zapata-Cachafeiro, Maruxa; Aguirre, Carmelo; Ibarra-García, Eguzkiñe; Palacios-Zabalza, Itziar; Macías-García, Fernando; Piñeiro-Lamas, María; Ibáñez, Luisa; Vidal, Xavier; Vendrell, Lourdes; Martin-Arias, Luis; Sáinz-Gil, María; et al.
Abstract: Background: Interindividual genetic variations contribute to differences in patients' response to drugs as well as to the development of certain disorders. Patients who use non-steroidal anti-inflammatory drugs (NSAIDs) may develop serious gastrointestinal disorders, mainly upper gastrointestinal haemorrhage (UGIH). Studies about the interaction between NSAIDs and genetic variations on the risk of UGIH are scarce. Therefore, we investigated the effect of 16 single nucleotide polymorphisms (SNPs) involved in drug metabolism on the risk of NSAIDs-induced UGIH. Materials and methods: We conducted a multicenter case-control study of 326 cases and 748 controls. Participants were sub-grouped into four categories according to NSAID exposure and genetic profile. We estimated odds ratios (ORs) and their 95% confidence intervals (CI) using generalized linear mixed models for dependent binomial variables and then calculated the measures of interaction, synergism index (S), and relative excess risk due to interaction (RERI). We undertook stratified analyses by the type of NSAID (aspirin, non-aspirin). Results: We observed an excess risk of UGIH due to an interaction between any NSAID, non-aspirin NSAIDs or aspirin and carrying certain SNPs. The greatest excess risk was observed for carriers of: rs2180314:C>G [any NSAID: S  = 3.30 (95%CI: 1.24–8.80), RERI = 4.39 (95%CI: 0.70–8.07); non-aspirin NSAIDs: S  = 3.42 (95%CI: 1.12–10.47), RERI = 3.97 (95%CI: 0.44–7.50)], and rs4809957:A>G [any NSAID: S  = 2.11 (95%CI: 0.90–4.97), RERI = 3.46 (95%CI: −0.40–7.31)]. Aspirin use by carriers of rs6664:C>T is also associated with increased risk of UGIH [ORaspirin(+), wild-type : 2.22 (95%CI: 0.69–7.17) vs. ORaspirin(+), genetic-variation : 7.72 (95%CI: 2.75–21.68)], yet larger sample size is needed to confirm this observation. Conclusions: The joint effect of the SNPs s2180314:C>G and rs4809957:A>G and NSAIDs are more than three times higher than the sum of their individual effects. Personalized prescriptions based on genotyping would permit a better weighing of risks and benefits from NSAID consumption. KEY MESSAGES: Multicenter case-control study of the effect of genetic variations involved in drug metabolism on upper gastrointestinal haemorrhage (UGIH) induced by NSAIDs (aspirin and non-aspirin). There is a statistically significant additive synergism interaction between certain genetic polymorphisms and NSAIDs on UGIH: rs2180314:C>G and rs4809957:A>G. The joint effect of each of these single nucleotide polymorphisms and NSAIDs on UGIH is more than three times higher than the sum of their individual effects. Genetic profiling and personalized prescriptions would be useful in managing the risks and benefits associated with NSAIDs.